Peran Media Massa dan Teknologi dalam Transformasi Keintiman di Indonesia - Rinta Arina Manasikana; Ratna Noviani (School of Communication Science and Media Business, 2021)
This research aimed to identify how the current development in technology and mass media is affecting the form and the way people fulfill intimacy in Indonesia by using Anthony Giddens' concept of intimacy transformation. In his book The Transformation of Intimacy Sexuality, Love, and Eroticism in Modern Societies (1992), Giddens stated that there are changes in intimacy relations in society from time to time which are influenced by the pace of modernity. This research showed that there are influences from mass media and technology in changing concept of intimacy and how to fulfill it in society, where previously only recognizing the concept of matchmaking and marriage as way to fulfill it, are now beginning to shift in other ways, such as the use of matchmaking columns in mass media, online dating applications, to the internet and games. However, patriarchal culture is something that still limits change with all existing stereotypes and rules, especially for women. This reflected in the negative stigma of their active role and the potential for sexual harassment in cyberspace when fulfilling intimacy. Keywords: mass media, intimacy, transformation of intimacy, Anthony Giddens